Activity of Monooxygenase and Nitrogenous Systems in Liver Microsomes Under the Influence of Inducers and Inhibitors of Medicinal Metabolism on the Organism in Conditions of Liver Pathology - Saida, Sayfullaeva; Alisher, Okhunov; Nargiza, Jumanova (International Journal of Psychosocial Rehabilitation, 2020)
In experiments on 48 white-breed rats of males with a mass of 180-250 g. it was found that benzenol in an effective dose of 75 mg/kg had a favorable effect on the monooxygenase and nitration system of hepatocyte microcircuits of rats with acute liver damage, while cimetidine in a dose of 10 mg/kg further suppressed the activity of MCO, increased the formation of toxic radicals NO, leading to an even greater aggravation of the severity of the animals.